The effect of partial retirement on labor supply, public balances and the income distribution: Evidence from a structural analysis - Songül Tolan (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper develops a structural dynamic retirement model to investigate effects and corresponding underlying mechanisms of a partial retirement program on labor supply, fiscal balances, and the pension income distribution. The structural approach allows for disentangling the two counteracting mechanisms that drive the employment effects of partial retirement: 1) the crowding-out from full-time employment, and 2) the movement from early retirement or unemployment to partial retirement. It also allows for investigating the role of financial compensations in a partial retirement program. Based on a unique German administrative dataset, I perform counterfactual policy simulations that analyze the role of partial retirement combined with financial subsidies and an increased normal retirement age. The results show that partial retirement extends working lives but reduces the overall employment volume. The fiscal consequences of partial retirement are negative but substantially less so when wages and pensions in partial retirement remain uncompensated. Partial retirement decreases inequality in pension income and provides a way to smooth consumption especially for retirees in lower income deciles in the context of an increased normal retirement age.
Keywords: C61; J26; H55; 330; Retirement; Partial Retirement; Social Security and Public Pensions; Structural estimation; Dynamic Discrete Choice